2012
DOI: 10.1271/bbb.110873
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Flavonols inGinkgo bilobaProducts by Ultra-High-Performance Liquid Chromatography Coupled with Ultra-Violet Detection and Time-of-Flight Mass Spectrometry

Abstract: The aim of this study was to survey the flavonol compositions of Ginkgo biloba products, especially those on the Japanese market. Sixteen food products, six medicinal products, and raw Ginkgo biloba leaves were examined by ultra-high-performance liquid chromatography coupled with ultra-violet detection and time-offlight mass spectrometry. Eleven flavonol glycosides, three biflavones, and a flavonol aglycone were qualified by analysis of accurate mass spectra. The quantitative data obtained were then applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…A Dutch study showed similarly strong differences in quality among 29 ginkgo products ( Fransen et al, 2010 ). Significant differences in quality between various G. biloba preparations were also found in a Japanese study ( Kakigi et al, 2012 ). Among the preparations analyzed in a Polish study, products were found containing relatively small amounts of flavone glycosides or terpene lactones, but with ginkgolic acid concentrations of up to 392 ppm ( Gawron-Gzella et al, 2010 ).…”
Section: The Results Generated By the Processsupporting
confidence: 54%
“…A Dutch study showed similarly strong differences in quality among 29 ginkgo products ( Fransen et al, 2010 ). Significant differences in quality between various G. biloba preparations were also found in a Japanese study ( Kakigi et al, 2012 ). Among the preparations analyzed in a Polish study, products were found containing relatively small amounts of flavone glycosides or terpene lactones, but with ginkgolic acid concentrations of up to 392 ppm ( Gawron-Gzella et al, 2010 ).…”
Section: The Results Generated By the Processsupporting
confidence: 54%
“…Furthermore, eight PFS showed amounts of quercetin, kaempferol, and isorhamnetin that suggested adulteration with synthetic aglycones (Avula, Sagi, Gafner, et al, 2015). Kakigi et al (2012) used a similar targeted analysis based on profiling 15 compounds (11 flavonol glycosides, three biflavones, and quercetin) by UHPLC-UV-TOF-MS. However, the approach was slightly different since it did not comprise full quantification of the compounds.…”
Section: Liquid Chromatographymentioning
confidence: 99%
“…During the course of our research on the origins of natural products using morphological, genomic, and chemical analyses, we found that the ingredients of some of the following health food products did not originate from the material listed on the label: chondroitin sulfate [ 51 ], white kwao keur ( Pueraria candollei var. mirifica ) [ 52 ], black cohosh [ 53 , 54 ], haru-ukon ( Curcuma aromatica ) [ 55 ], bilberry [ 56 ], ginkgo leaf [ 57 ], chaste berry [ 58 ], and herbal materials for foodstuffs, such as Isodonis Herba and Isodonis extracts [ 59 ] and Sida products [ 60 ]. The average ratio of wrongly labeled products, including those with constituents from the stated origin but containing adulterants, to correctly labeled products was approximately one-third [ 61 ].…”
Section: Regulatory Science Of Borderline Productsmentioning
confidence: 99%
“…The results tested by the National Consumer Affairs Center of Japan for health food products of chondroitin sulfate and α-lipoic acid also showed a similar ratio in 2008. Furthermore, chromatographic analyses revealed that the content range of active ingredients in health foods, such as bilberry [ 56 , 62 ], vine leaf [ 63 ], ginkgo leaf [ 57 ], and chaste berry [ 58 ], is wider than that of pharmaceutical products.…”
Section: Regulatory Science Of Borderline Productsmentioning
confidence: 99%